Quality of Life in Stroke Patients Using SSQoL Scale and Barthel Index - Mudaliar, Mohanraj Rathinavelu; Yiragamreddy, Samhitha Reddy; Tejashwani, Priyanka Pichala; Umapathi, Sowjanya; Sake, Nagamani; Sharma, Sreedhar (Indian Journal of Pharmacy Practice)
Introduction: Stroke is a major catastrophic event majorly defining morbidity and mortality in patients. The assessment of quality of life after stroke is becoming common with the recognition that evaluation of treatment should include quality as well as quantity of survival. Materials and Methods: The current prospective, observational study of six months duration was performed to assess the quality of life in stroke inpatients of a tertiary care teaching hospital in south India using SSQoL scale and Barthel Index. The study participants were interviewed based on 12 domains and 49 items of SSQoL scale and 10 questions from Barthel index. Results: Out of 48 stroke inpatients, 62.5% were male and 37.5% female, furthermore there was equal distribution of patients with respect to gender within age groups of 56-60 and 61-65 years. The changes in quality of life observed in all stroke inpatients using SSQoL scale and Barthel Index with respect to associated complications was found to be higher in hypertension populations, patients with tobacco and pan chewing habit was observed as primary risk factor for stroke attacks, and patients with 1st episode without accident proved more risk for stroke attack. Conclusions: In conclusion, improved methods to measure the quality of life in stroke are required. Quality of life measures must be valid, reliable, responsive and comprehensive; and also with the involvement of patients at every stage of measure. Performing an exemplary and extensive research studies on stroke and its quality of life could bring better health outcome in individual patients.
Keywords: Cerebro vascular accidents; Barthel Index; Inpatients; Quality of life; SSQoL.